A Short Synthesis of the Plant Alkaloid 4-Methyl-2,6-naphthyridine - Kamlah, Alexandra; Bracher, Franz (Letters in Organic Chemistry, 2019)
A new synthesis of the 2,6-naphthyridine alkaloid 4-methyl-2,6-naphthyridine from Antirrhinum majus has been developed. Key steps are a regioselective oxidation of 3-bromo-4,5- dimethylpyridine to the corresponding 4-formyl derivative, and the annulation of the second pyridine ring by Suzuki-Miyaura cross-coupling using (E)-2-ethoxyvinylboronic acid pinacol ester as a masked acetaldehyde equivalent. This protocol gives the alkaloid in four steps starting from commercially available 3,4-dimethylpyridine in 15% overall yield. This annulation protocol should be useful for the synthesis of other condensed pyridines as well.
Keywords: enol ether